Analisis Perumusan Strategi pada Unit Bisnis Perusahaan Umum Perhutani Garut - Sofian Munawar (Fakultas Ekonomi Universitas Garut, 2018)
This study aims to determine the factors that affect business units existing in the public company perhutani either from external or internal company, then what steps should be done to respond to these factors, and what strategies should be applied to existing business units In general company perhutani KPH Garut. The research method used is descriptive method, data collection techniques used are observation, interview, questionnaire, Literature and research documentation. The data source used is Primary data that is result of interview scheme with some policy holder in company. Data processing techniques used are external matrix factor evaluation (EFE), internal factor evaluation (IFE) matrix, strength-weakness-opportunity-threat (SWOT) matrix, and internal-external (IE) matrix. The result of the research recommends strategies for the three business units that are timber forest products (HHK), non-timber forest products (HHBK) and tourism business units are intensive strategy that is market penetration strategy, product development (product / innovation), combined With a defensive strategy that is retrenchment strategy (shrinkage or cost savings).